Absensi Elektronik dan Keterasingan Akademik di Perguruan Tinggi - Husain, Wahyuni; Ashabul, Muhammad; Ibrahim, Intan Soliha (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2024)
This study aims to analyze the implementation of electronic attendance through fingerprinting as a disciplinary instrument for lecturers at IAIN Palopo. This research employs Michael Foucault's theory of power to reveal the model of power relations manifested through the fingerprint mechanism and its impact on lecturers. The methods used in this study include observation, interviews with lecturers, and document analysis. The findings indicate that every lecturer at IAIN Palopo is required to use fingerprint attendance every working day, even if they do not have a teaching schedule every day. This system creates two main mechanisms of power relations. First, hierarchical surveillance is conducted through attendance machines, CCTV, leadership, and the Monthly Lecturer Performance Sheets. Second, the mechanism of performance allowances is paid based on the monthly attendance recap. Surveillance through fingerprinting and CCTV allows the management to strictly monitor lecturers' attendance, ensuring discipline in terms of presence. However, although this system effectively increases attendance, some negative impacts have been identified. Lecturers become more focused on their physical presence rather than on other important tasks such as research and community service. This indicates that the power relations enforced through electronic attendance successfully create discipline in attendance but do not address other aspects of lecturers' duties. Thus, the implementation of electronic attendance through fingerprinting at IAIN Palopo reflects a complex form of power, where discipline is achieved through strict surveillance and financial incentives, but other important elements of academic performance are neglected. This study provides important insights into how technology can be used to regulate behavior in educational settings and the implications of such technology on various aspects of lecturers' performance.